2012
DOI: 10.1097/mou.0b013e328358e191
|View full text |Cite
|
Sign up to set email alerts
|

Varicocele repair in the era of modern assisted reproductive techniques

Abstract: Varicocele correction presents a possible method to optimize a couples' reproductive potential or decrease the need for complex assisted reproductive technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 25 publications
0
8
0
3
Order By: Relevance
“…The effects of the correction of varicocele on sperm quality and reproductive potential are less well understood. Clinical research has demonstrated improved semen parameters, higher DNA integrity, and better assisted reproductive technology outcomes after varicocele repair [24]. …”
Section: Discussionmentioning
confidence: 99%
“…The effects of the correction of varicocele on sperm quality and reproductive potential are less well understood. Clinical research has demonstrated improved semen parameters, higher DNA integrity, and better assisted reproductive technology outcomes after varicocele repair [24]. …”
Section: Discussionmentioning
confidence: 99%
“… 6 7 14 15 However, it is unclear whether performing varicocelectomy in infertile males with clinical varicocele prior to ART improves treatment outcomes. 16 …”
Section: Introductionmentioning
confidence: 99%
“…Recent papers have justified the increase of testicular volume for intratesticular interstitial edema, but other follow-up reveal this is because of a real growth of testis that improves with time (25,26). Many cases in the literature showed improvement in sperm quality after varicocelectomy; however, the data are few because spermiogram analysis cannot be obtained at pediatric age (27). Mancini et al in 2014 have also to analyzed the volume of testis and the quality of semen in patients treated with both minimally invasive approaches (transperitoneal approach and retroperitoneoscopy approach) (21).…”
Section: Resultsmentioning
confidence: 99%